Acute myeloid leukemia cells MOLM-13 and SKM-1 established for resistance by azacytidine are crossresistant to P-glycoprotein substrates. Issue 7 (October 2015) - Messingerova, Lucia; Imrichova, Denisa; Kavcova, Helena; Turakova, Katarina; Breier, Albert; Sulova, Zdena
Highlights Multidrug resistant SKM-1 and MOLM-13 cell variants by selection with azacytidine were established. Induction of P-glycoprotein and glutathione S-transferase in resistant cell variants were proved. Altered expressions of antiapoptotic and proapoptotic proteins in resistant variant of cells were observed. Resistant variants of SKM-1 and MOLM-13 cells exert depressed sensitivity to AzaC and P-gp substrates.